Total Syntheses of Basiliolide A1, Basiliolide A2, Basiliolide C, and their Structural Analogues. Issue 2 (16th January 2018) - Ma, Wenjing; Liang, Xuefeng; Ye, Wejian; Wang, Yuena; Min, Long; He, Shuzhong; Lee, Chi‐Sing
Abstract : A small focussed library of basiliolides including basiliolide A1, basiliolide A2, basiliolide C, and their structural analogues have been prepared for structure–activity‐relationship studies. The synthesis features a cyclopropanation/ring‐opening strategy to establish the C‐8 stereogenic centre by using the cyclopropanation substrate with the appropriate alkene geometry; an IMDA (intramolecular Diels–Alder) reaction to construct the seco acid derivatives; and a biomimetic O ‐acylation to form the unprecedented seven‐membered acyl ketene acetal ring. The des‐D‐ring analogues were prepared by an IMDA/decarboxylation strategy. Moreover, an asymmetric catalytic cyclopropanation reaction has been developed; this provided an optically enriched intermediate for asymmetric synthesis. Abstract : A small focussed library of basiliolides including basiliolide A1, basiliolide A2, basiliolide C, and their structural analogues has been prepared for structure–activity‐relationship studies.